2002
DOI: 10.1053/jhep.2002.30274
|View full text |Cite
|
Sign up to set email alerts
|

TIPS is a useful long-term derivative therapy for patients with Budd-Chiari syndrome uncontrolled by medical therapy

Abstract: Patients with Budd-Chiari syndrome (BCS) may require treatment with portal decompressive surgery or liver transplantation. Transjugular intrahepatic portosystemic shunt (TIPS) represents a new treatment alternative, but its long-term effect on BCS outcome has not been evaluated. Twenty-one patients with BCS consecutively admitted to our unit were evaluated. The mean follow-up was 4 ؎ 3 years. Seven patients had nonprogressive forms and were successfully controlled with medical therapy; 1 case, with a short-len… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
119
3
10

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(134 citation statements)
references
References 42 publications
2
119
3
10
Order By: Relevance
“…Other recent studies have demonstrated positive results of this new approach in terms of short-term survival. 12,13,26 TIPS is less invasive and therefore probably associated with a lower procedural mortality than PSS. 27 Long-term follow-up studies are needed to assess the place of TIPS in the treatment of BCS.…”
Section: Discussionmentioning
confidence: 99%
“…Other recent studies have demonstrated positive results of this new approach in terms of short-term survival. 12,13,26 TIPS is less invasive and therefore probably associated with a lower procedural mortality than PSS. 27 Long-term follow-up studies are needed to assess the place of TIPS in the treatment of BCS.…”
Section: Discussionmentioning
confidence: 99%
“…In the last decade, the use of TIPS in BCS is increasingly described in the world literature [81][82][83][84][85][86][87][88][89][90][91][92][93][94] . In cases with severe liver dysfunction requiring liver transplantation, TIPS used as an interim bridge to transplantation, can improve the situation dramatically [4] .…”
Section: Discussionmentioning
confidence: 99%
“…TIPS has been shown to be effective as the treatment for BCS in early experiences [21][22][23] and can be successful also in the technically difficult case of extension of thrombosis to the portal vein tree [24,25] . Moreover, a multi-center experience provided long-term data on TIPS treatment for 147 BCS patients not responding to medical treatment or recanalization.…”
Section: Treatments For Budd-chiari Syndromementioning
confidence: 99%